RANCANG BANGUN SISTEM E-COMMERCE MENGGUNAKAN METODE MARKETING MIX UNTUK MEMPERLUAS PANGSA PASAR PADA TOKO DEWI LAMPUNG SELATAN - Iis Meilinda (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2022)
Toko Dewi Pasuruan is a store engaged in electronic sales located on Jl. Pasuruan Dusun Pasuruan Atas, Pasuruan Village, Penengahan District, South Lampung Regency. This store is one of the largest electronic stores in Penengahan District, South Lampung. The interview that the author conducted with Mrs. Herlina Wati as the owner of the store showed that there were several problems in this store such as recording and inadequate to carry out remote services. In the business world, there are various marketing strategies that can improve service in sales, one of which is called the marketing mix. One of the applications of this marketing mix can be done by implementing E-commerce. Where with the application of E-commerce can support the increase in prouct variables where the scale of providing information about the products sold becomes wider The results of the research carried out have succeeded in building E-commerce that can be applied as a marketing mix or marketing mix at Toko Dewi. Where E-commerce is able to accelerate remote services. In addition, the test results of ISO 25010 showed that the E-commerce that was built was declared Very Feasible for use with the results of the Test Score on the aspect of Functional Suitability reaching a value of 98.70%.